Seasonal Metabolic Investigation in Pomegranate (Punica granatum L.) Highlights the Role of Amino Acids in Genotype- and Organ-Specific Adaptive Responses to Freezing Stress - Yazdanpanah, Parisa; Jonoubi, Parisa; Zeinalabedini, Mehrshad; Rajaei, Homa; Ghaffari, Mohammad Reza; Vazifeshenas, Mohammad Reza; Abdirad, Somayeh (Frontiers in Plant Science, 2021)
Every winter, temperate woody plants have to cope with freezing stress. Winter hardiness is of crucial importance for pomegranate survival and productivity. A comparative morphological and metabolic study was conducted on stem and bud of fifteen field-grown mature pomegranate genotypes in seven time-points during two developmental cycles. Seasonal changes of frost hardiness, as determined by electrolyte leakage method, and metabolite analysis by HPLC and GC revealed the variability in frost hardiness and metabolic contents result from genetic background and organ, as well as seasonal condition. Morphological adaptations, as well as metabolic remodeling are the distinct features of the hardy genotypes. Larger buds with the greater number of compressed scales and the higher number of protective leaves, together with the higher number and content of changed metabolites, especially amino acids, seem to provide a higher frost resistance for those trees. Two-times change in metabolites and several-times accumulation of amino acids recorded in the stem, compared with buds. A better potential of stem for metabolome adjustment during hardening period and a higher level of tolerance to stress is therefore suggested. High levels of arginine, proline, glutamine and asparagine and particularly accumulation of alanine, tryptophan and histidine can be responsible for excellent tolerance of the stem of tolerant genotypes. With regard to protective roles of amino acids, a relation between stress tolerance and the level of amino acids is proposed. This fact points both to the importance of amino acids in winter survival of pomegranate tree, and to the evaluation of frost tolerance in other plants, by these specific markers.